Correlation of Cleanliness among Different Bowel Segments during Colonoscopy: A Retrospective Study - Zhou Haibin; Zhang Xiaofeng; Yang Jianfeng (Gastroenterology Research and Practice)
Objective. To analyze the correlation of intestinal cleanliness in each segment of the Boston Intestinal Preparation Scale. Methods. From February 2017 to October 2019, the data of patients who underwent colonoscopy in the Department of Gastroenterology, Hangzhou First People’s Hospital, Zhejiang University School of Medicine, were collected. Statistical analysis was performed according to the Boston Intestinal Preparation Scale score, and the correlation of intestinal cleanliness in each region was obtained. Results. A total of 1739 patients were included. The overall score of BBPS was 6.77±1.88. The scores of each region were 2.04±0.84 (right lateral colon), 2.25±0.68 (transverse colon), and 2.48±0.64 (left colon). The difference between the regions was statistically significant (P<0.05). The bowel cleanliness showed a gradual deterioration trend, and there was a positive correlation between colon cleanliness in each region. The accuracy of the transverse colon in predicting the right colon (AUC=0.809) is higher than that of the left colon (AUC=0.735), and the accuracy of predicting the cleanliness of the right colon intestinal tract by the cleanliness of the left colon intestinal tract is relatively low. Conclusion. Intestinal cleanliness gradually deteriorates from the direction of the insert. It is not reliable to predict the right side of poor cleanliness by using the left colon intestinal cleanliness (BBPS 0-1 score). It should continue to further endoscopy. When the cleanliness of the transverse colon is poor, then stopping further endoscopy is considered.